2017
DOI: 10.1044/2016_jslhr-l-16-0201
|View full text |Cite
|
Sign up to set email alerts
|

Increased Response to Altered Auditory Feedback in Dyslexia: A Weaker Sensorimotor Magnet Implied in the Phonological Deficit

Abstract: a Purpose: The purpose of this study was to examine whether developmental dyslexia (DD) is characterized by deficiencies in speech sensory and motor feedforward and feedback mechanisms, which are involved in the modulation of phonological representations. Method: A total of 42 adult native speakers of Dutch (22 adults with DD; 20 participants who were typically reading controls) were asked to produce /bep/ while the first formant (F1) of the /e/ was not altered (baseline), increased (ramp), held at maximal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 97 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…Recently, an auditory feedback paradigm was used in Dutch adults with and without dyslexia to examine whether speech perception-production interactions are affected in people with dyslexia (Van Den Bunt et al, 2017). In that study, participants were asked to repeatedly produce the nonword /bɛp/ while the frequency of the first formant of the /ɛ/ sound was unaltered in the baseline phase, gradually manipulated to a 25% increase during the ramp phase, held at maximum (25%) during the hold phase, and again unaltered in the after-effect phase.…”
Section: Altered Auditory Feedback and Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an auditory feedback paradigm was used in Dutch adults with and without dyslexia to examine whether speech perception-production interactions are affected in people with dyslexia (Van Den Bunt et al, 2017). In that study, participants were asked to repeatedly produce the nonword /bɛp/ while the frequency of the first formant of the /ɛ/ sound was unaltered in the baseline phase, gradually manipulated to a 25% increase during the ramp phase, held at maximum (25%) during the hold phase, and again unaltered in the after-effect phase.…”
Section: Altered Auditory Feedback and Dyslexiamentioning
confidence: 99%
“…These results were interpreted in light of the "perceptual magnet" theory (Feldman, Griffiths, & Morgan, 2009;Kuhl, 1991), which claims that a phonetic category prototype functions as a magnet that results in relatively poorer discriminability for neighboring stimuli close to the prototype and better discriminability for stimuli that are farther away from the prototype. With respect to the response to altered auditory feedback in dyslexia, a weaker magnet could increase the response to alterations in altered auditory feedback (when the percept deviates from the phonetic category prototype) and reduce the ability to reestablish the representations when feedback is back to normal (Van Den Bunt et al, 2017). Although these findings indicate that adults with dyslexia respond differently to altered auditory feedback-which might indicate an impairment in speech feed-forward and feedback mechanisms-several issues remain: 1) To what extent is a stronger response to altered auditory feedback characteristic of children, as it was found to be of adults, with dyslexia; 2) How does the response to altered auditory feedback relate to individual differences in reading and reading-related skills.…”
Section: Altered Auditory Feedback and Dyslexiamentioning
confidence: 99%
“…Given a sensorimotor adaptation dataset, optimal values of these parameters for fitting the data are derived (i.e., are data-driven); the resulting parameters provide an estimate of the relative roles of the three different control subsystems in the corresponding experiment. For the purposes of the current article, we focus on adaptation experiments involving auditory feedback perturbations, though in principle the same model can be used to analyze the results of adaptation experiments involving somatosensory perturbations applied to the speech articulators (e.g., Tremblay et al, 2003;Nasir and Ostry, 2006) as well as experiments involving perturbations to both auditory and somatosensory feedback (Feng et al, 2011;Lametti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although these mechanisms are shown to be crucially involved in phonological representations, they have not yet been adequately examined in emergent readers. In a recent study, we examined the sensorimotor control of speech using an altered auditory feedback paradigm to probe the quality of phonological representations in adults (Van Den Bunt et al, 2017). We argued that this sensorimotor control of speech is crucially involved in the adequate development of phonological representations (Guenther et al, 2006;Hickok et al, 2011) and directly reflects phonological processes, in contrast to measures such as phonological awareness, that also entail metalinguistic processing (Van Den Bunt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we examined the sensorimotor control of speech using an altered auditory feedback paradigm to probe the quality of phonological representations in adults (Van Den Bunt et al, 2017). We argued that this sensorimotor control of speech is crucially involved in the adequate development of phonological representations (Guenther et al, 2006;Hickok et al, 2011) and directly reflects phonological processes, in contrast to measures such as phonological awareness, that also entail metalinguistic processing (Van Den Bunt et al, 2017). We found that adults with dyslexia responded differently in an altered auditory feedback task in which we changed the first formant 1 of the /ɛ/ vowel in the participants' production in the direction of the English /ae/ vowel.…”
Section: Introductionmentioning
confidence: 99%